(untitled) (Research, Society and Development, 2020)
The present study aimed to investigate how the principles of transparency and universalization of access to basic sanitation provided for in Federal Law No. 11,445 of 2007, which provides for the National Basic Sanitation Plan, have been fulfilled and achieved in the municipalities of the state of Pará for the water supply and sewage collection services. For this, data made available by the municipalities of Pará were obtained and analyzed in the database of the National Sanitation Information System. The results show that the principle of transparency has not been fulfilled by most of these municipalities because of the lack of data submission or continuity of these. Regarding the universalization of access, it was perceived that the municipalities of Pará analyzed are going along a path contrary to this principle in relation to the service of drinking water supply, while for the collection of sanitary sewage, the municipalities whose analysis was possible to perform, presented small advances.